Impact of Pricing and Product Information on Consumer Buying Behavior With Customer Satisfaction in a Mediating Role - Zhao, Huiliang; Yao, Xuemei; Liu, Zhenghong; Yang, Qin (Frontiers in Psychology, 2021)
The relationship between product pricing and product packaging plays an important role in consumers’ buying behavior, while customer satisfaction plays a mediating role. To test these hypotheses, research was conducted on university students in China. Questionnaire-based convenience sampling was conducted on 500 students for data collection, using online and offline sources. A total of 367 (73%) students responded, and 17 questionnaires were rejected due to missing information. SPSS and AMOS software were used for the data analysis. Product pricing and product information were independent variables in this study, while consumer buying behavior was a dependent variable. Customer satisfaction is mediated by one dependent and two independent variables. Confirmatory factor analysis, path analysis, and discriminant validity in structural equation modeling revealed that product pricing and packaging had a statistically significant relationship with the buyer decision process. The introduction of satisfaction as a mediating variable led to the observation of full mediation in the case of product pricing and partial mediation in product packaging. Given the results of this research, product managers should adopt pricing tactics along with product packaging to influence consumers’ buying intentions.